DETERMINAN KEBERMAKNAAN KERJA PADA PERAWAT : LITERATUR REVIEW - Andiarto, Afri; Matin, Nur Sophia; Khoiriyah, Imas Elva (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2024)
Nursing is a profession that is constantly changing and taking on new roles amidst existing challenges, including the COVID-19 pandemic where nurses are at the forefront of handling it. The meaning of work is an important part of supporting nurses to keep working well in the midst of a pandemic. This study aims to look at the factors that determine the level of meaningful work in nurses. This research method uses the literature review method with the Google Scholar database of 5 articles with a time span of 2019-2023. The findings show that the determinants of the meaningfulness of work for nurses include two factors, internal and external. Internal is represented by gender, work belief, motivation, personality, and psychological state. While external factors include working conditions, conformity of organizational values, and togetherness. It is important to increase the meaningfulness of work for nurses by using approaches that are relevant to the results of this study.